The effect of compaction pressure and addition of silica on microstructure, thermal property and mechanical strength of polyurethane-silica RHA composite - Juliana Abdul Ghani, 1987-; Muhamad Azizi Mat Yajid, supervisor; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2014